Cytotoxic neo-clerodane diterpenes from Stachys aegyptiaca. (December 2018) - Mohamed, Tarik A.; Elshamy, Abdelsamed I.; Hamed, Ahmed R.; Shams, Khaled A.; Hegazy, Mohamed-Elamir F.
Graphical abstract: Highlights: From the medicinal herb Stachys aegyptiaca, an organic extract was chemically investigated. Two new diterpenoids were identified via spectroscopic methods. Four purified diterpenoids exhibited cytotoxic activity against a carcinoma cell line. Abstract: Two new E/Z neo -clerodane diterpene isomers, trivially named stachaegyptin D (1 ) and E (2 ), together with known compounds, stachysolon monoacetate (3 ) and stachysolon diacetate (4 ), were isolated from an organic-solvent extract of the medicinal herb Stachys aegyptiaca . Structures were elucidated by a combination of spectroscopic methods, including HREIMS, 1 H, 13 C, DEPT, and 2D NMR analysis, as well as, first time X-ray analysis for stachysolone (3 ). All isolated metabolites showed some activity against the human hepatocellular cell line, HepG2. Compound4 was the most active with an IC50 of 59.5 μM.